Examining Student Reported Interaction and Satisfaction in Higher Education Administration Graduate Seminar-Style Blended Courses - Thurber, Derek; Trautvetter, Lois (Online Learning, 2020)
The purpose of this case study was to examine how a professional graduate program in higher education administration developed seminar-style courses in a blended format. Blended courses involved two extended in-person weekend sessions with synchronous online sessions, and other asynchronous coursework in between. This study explored the importance of interaction, student satisfaction, and motivation to student success. Data were collected through student surveys and faculty interviews from 11 courses within the same graduate degree program at a private, highly-selective research university from spring 2016 through spring 2018. Class size was the biggest factor relating to student interaction. This study also found synchronous online discussions had a greater impact than other learning activities and that satisfaction and interaction had a slight increase over time as students and instructors became more comfortable with the format.